Is language essential? Exploring the role of language on deciding whether to localise or standardise an international advertising campaign. - Gkortsila, Marianna (2015)
The growing globalisation and cultural convergence that have been observed during the last decades have given way to a rising dominance of the English language as the language of global communications. This is hypothesised to lead to a renewal of the always prominent standardisation debate in international marketing theory and practice. The present study seeks to explore consumers’ perceptions in a cross-cultural and cross-linguistic setting (UK and Greece) concerning international advertising standardisation and the use of English in it. For this purpose, qualitative interviews were conducted with the aid of some visual material (a standardised advertisement in English). Findings suggest that consumers are becoming increasingly familiar with the presence of foreign elements in advertising and with English in international advertisements. This confirms the hypothesis that English can play a unifying role and facilitate international advertising standardisation.